A permanent magnet alternator with increased power capability for hybrid electric vehicle applications - Ayaz, Murat; Mese, Erkan (ELSEVIER SCIENCE SA, 2016)
In this study, a new permanent magnet alternator is proposed in an effort to increase its power capability. The new alternator relies on an auxiliary winding sharing the same slots with the main alternator winding. The main alternator winding is connected to a 12 Volt DC bus through an uncontrolled rectifier. The auxiliary winding, which is called control winding throughout the study, is connected to a 300 Volt DC bus through a DC/AC inverter which enables full control over the winding current. Both main and auxiliary windings have fractional slot concentrated type coils in order to reduce mutual coupling among them. With the proposed structure, it is possible to extend the constant torque region to higher speed, thus enabling greater power output from the machine. Furthermore, the proposed method enables to obtain better voltage regulation by flux strengthening at low speed region where normally it would not be possible due to low back EMF. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Active output voltage regulation; Dual winding PM machine; Flux weakening; Hybrid electrical vehicle applications; Permanent magnet synchronous generator (PMSG); MACHINES; Engineering